Klotho protects INS-1 pancreatic β-cells from senescence and enhances mitochondrial function - Wang, Zhihong; Ni, Yunzhi; Lou, Yan-Ru; Prud’homme, Gerald J.; Wang, Qinghua (Frontiers in Aging, 2025)
Aging is an important contributing factor for β-cell failure which could lead to the development of type 2 diabetes (T2D). Aging β-cell exhibits signs of senescence and develops senescence-associated secretory phenotype (SASP), causing the senescence and dysfunction of neighboring cells through paracrine action. Klotho is recognized as an anti-aging gene, and the corresponding protein is α-Klotho (KL). KL exerts potent anti-aging effects on multiple cell types, but its role in β-cell aging remains unclear. Here we showed that pancreatic INS-1 cell (a rat insulinoma cell line commonly used to study pancreatic β-cell function) developed the typical hallmarks of senescent cells when treated with doxorubicin in vitro, and this was accompanied by downregulation of endogenous KL expression. Supplementation with exogenous KL protein protected pancreatic INS-1 cell against senescence, as indicated by downregulation of senescent markers and SA-β-gal staining. Notably, these effects were associated with improved mitochondrial ATP production and mitochondrial dynamic balance, as well as reduced ROS production. Our study further revealed that INS-1 cell treated with doxorubicin exhibited a reduced insulin secretion response to glucose stimulation, while supplementation with KL could reverse this effect. Our results indicate the important role of KL in regulating β-cell senescence and provide new mechanistic insights into its role in β-cell aging.